2020
DOI: 10.1038/s41598-020-74600-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal intrauterine growth restriction and risk of retinopathy of prematurity

Abstract: Low birthweight and decreased postnatal weight gain are known predictors of worse retinopathy of prematurity (ROP) but the role of prenatal growth patterns in ROP remains inconclusive. To distinguish small for gestational age (SGA) from intrauterine growth restriction (IUGR) as independent predictors of ROP, we performed a retrospective cohort study of patients who received ROP screening examinations at a level IV neonatal intensive care unit over a 7-year period. Data on IUGR and SGA status, worst stage of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…In the present study we have found a strong association of fetal growth retardation with ROP disease. In literature, it has been found that the infants that have prenatal intrauterine growth retardation are at increased risk of developing severe ROP (Chu et al, 2020) Besides the placental size we have also found significant association of vascular changes at the maternal-fetal interface: distal villous hypoplasia, thin elongated villi, Tenny Parker changes, alternating area of small and short hyper mature villi with the disease. Along with these placental changes we have also found rare pathological changes in the placentas from the deliveries where infants developed ROP.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study we have found a strong association of fetal growth retardation with ROP disease. In literature, it has been found that the infants that have prenatal intrauterine growth retardation are at increased risk of developing severe ROP (Chu et al, 2020) Besides the placental size we have also found significant association of vascular changes at the maternal-fetal interface: distal villous hypoplasia, thin elongated villi, Tenny Parker changes, alternating area of small and short hyper mature villi with the disease. Along with these placental changes we have also found rare pathological changes in the placentas from the deliveries where infants developed ROP.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study we have found a strong association of fetal growth retardation with ROP disease. In literature, it has been found that the infants that have prenatal intrauterine growth retardation are at increased risk of developing severe ROP (Chu et al ., 2020)…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found inconsistent results for SGA being a risk factor for severe ROP. Filho et al [26] and Chu et al [37] found SGA not to be a risk factor for severe ROP, while Allegaert et al [28] reported SGA to be a risk factor for developing threshold ROP. However, a recent systematic review and meta-analysis found SGA to be associated with increased odds for severe ROP and suggested SGA to be considered in risk assessment of ROP evaluation [38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IUGR is a known factor for ROP, and a recent study retrospective cohort study by Chu et al demonstrated that IUGR infants were more likely to have a worse stage of ROP and treatment-requiring ROP compared to non-IUGR infants [ 26 ]. Additionally, it was demonstrated that a low 5-min Apgar score and an Apgar score of 6 or less at 5 min were significant risk factors for the manifested ROP to progress to stages requiring treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%